A108 USTEKINUMAB IV INDUCTION RESULTS IN CROHN'S DISEASE SYMPTOM IMPROVEMENT WITHIN THE FIRST WEEK IN ANTI-TNF REFRACTORY PATIENTS. (1st March 2018) - Sandborn, W; Yeager, B; Gasink, C; Hoops, T; Gao, L; Wang, Y; Jacobstein, D; Lee, S D; Hanauer, S
Abstract: Background: In both the UNITI-1&2 Crohn's disease (CD) studies, a single 6mg/kg Ustekinumab (UST) IV infusion showed significantly greater rates of clinical response & remission vs placebo, and significant reductions in CDAI (and >70 pt reduction) 1 by the first post-baseline visit at Wk 3. 2 Aims: It remains to be determined how soon patients see benefit (ie. before Wk 3). Methods: Patient (pt) CDAI diary daily data (day -7 to +14) from the UNITI-1 study of pts who had previously failed TNF antagonists were compiled and analyzed post-hoc for the 3 pt-reported CDAI components (stool frequency[SF], abdominal pain[AP], & general well-being[WB]). Mean change in these daily scores with IV UST 6 mg/kg and 130mg were compared vs. placebo (PBO), as were 2-item SF+AP PRO2 weekly, over the 7d prior, weighted either 1:1 or as a CDAI subscore (assessed by mean change, and as % of pts with >50pt improvement). Ranked transformation was used to compare groups for all analyses. Results: IV UST induced significant improvement in all 3 components within the first 2 wks, with AP first significantly better than PBO on d2 for both UST doses, and consistently significantly better than PBO from d6 through d14 for 6mg/kg and from d8 through d14 for 130mg. Mean improvement in SF was first significantly better than PBO on d7 for UST both doses, while this occurred on d8 for WB. Week 1 and 2 SF+AP with CDAI weighting was significantly improved for both UST doses vs PBO at d7 and d14, & SF+AP added with equal 1:1 weight was significantly improved for both UST doses at d14. 29.3% of 6mg/kg & 31.4% of 130 mg groups attained ≥50pt improvement in CDAI solely based on SF&AP components over the second week vs 18.8% in the PBO group (p<0.05 and p<0.01, respectively). Conclusions: Even in the refractory CD population of previous anti TNF failures in UNITI 1, symptom relief based on individual pt-reported CDAI components began to show significant improvement as early as 1 day post UST infusion, and was seen consistently among all 3 components by d8 with both IV UST doses, confirmed by consistent PRO2 benefit in the second week. These findings support previously reported significant early efficacy seen at the post-baseline (Wk3) visit in the UNITI induction studies. 2 1 Best WR, et al. Gastroenterology 1976;70:439–44 2 Feagan BG, et al. N Engl J Med 2016;375:1946–60 Funding Agencies: Janssen Research & Development, LLC funded this study